Investigating the use of information and communication technology (ICT) in village community banks (VICOBA) in southern Tanzania: Evidence from Songea Urban in the Ruvuma Region - Tossy, Titus (African Journal of Empirical Research, 2026)
The objective of this study is to investigate the use of Information and Communication Technology (ICT) in the operations of Village Community Banks (VICOBA) in Southern Tanzania, particularly in Songea urban in the Ruvuma region. For the past few years, VICOBA in the Ruvuma region has been using ICT in its operations; however, there is no documented research on this. This study sheds light on the matter, aiming to uncover the dynamics of its integration and utilization. The study was anchored with the Technology Acceptance Model (TAM) and the Technology Adoption and Diffusion of Innovations Theory (TADIT). Using a case study from Songea Urban in Southern Tanzania, the study employed an explanatory and analytical research design with a population of 40 respondents working in the VICOBA business. Both qualitative and quantitative data were collected using questionnaires, observations, and interviews. The collected data were examined and analyzed using the Statistical Package for the Social Sciences (SPSS) to identify patterns, trends, and correlations related to ICT usage in VICOBA. The study results revealed a diverse spectrum of ICT usage among VICOBA business operations; several ICT tools such as MKOBA, smartphones, laptops, projectors, etc. are widely used; 60% of the majority are satisfied with the use of ICT tools in various VICOBA activities; ICT within the VICOBA is primarily used for communication purposes (55%), and only 12.5% are using it for financial transactions and record keeping. The study also revealed several challenges in the use of ICT, including a lack of digital literacy, poor internet connectivity, security concerns, the high cost of technology, and others. However, the majority of VICOBA member groups perceive ICT’s usefulness, suggesting that VICOBA recognizes ICT’s potential to improve the efficiency and transparency of financial operations. These findings contribute to the existing knowledge by providing a detailed understanding of the intricate relationship between ICT and grassroots financial entities. The outcomes of this study are particularly relevant to policymakers and stakeholders involved in initiatives to foster financial inclusion and sustainable development in rural communities. In addition, these findings will help researchers and VICOBA groups.